The Selection of an Energy-Saving Engine Mode Based on the Power Delivery and Fuel Consumption of a 95 kW Tractor during Rotary Tillage - Md. Abu Ayub Siddique; Seung-Yun Baek; Seung-Min Baek; Hyeon-Ho Jeon; Jun-Ho Lee; Mo-A Son; Su-Young Yoon; Yong-Joo Kim; Ryu-Gap Lim (Agriculture, 2023)
The objective of this study was to estimate power delivery efficiency and fuel consumption based on engine modes. In this study, a 95 kW power-shift tractor was used to analyze power delivery and estimate fuel consumption during rotary tillage. Rotary tillage was conducted in a field experiment with the conventional, APS (auto power shift) power, and APS ECO engine modes. To analyze the field conditions, the soil hardness and soil water content were measured, and soil samples were collected from the experimental site to analyze the soil texture by using the USDA soil texture triangle. Finally, an efficient and suitable engine mode was selected for rotary tillage based on the working load. It was observed that the power delivery and tractive efficiencies when using the APS power mode were the highest among other engine modes, accounting for around 89.23 and 73.45%, respectively. However, the fuel consumption when using the APS power mode was approximately 23.02 L/h, which was also comparatively higher than that of the other engine modes. Additionally, the tractive efficiencies of each engine mode were compared using the Brixius prediction model. The statistical analysis of the predicted tractive efficiencies and those in the tests showed that there were no significant differences among the engine modes; this indicates that the APS controller could perform with high accuracy. In the conventional mode, the power delivery, tractive efficiency, and fuel consumption were approximately 66.48%, 55.89%, and 17.04 L/h, respectively, which were comparatively low. However, the slip ratio in the conventional mode was 18.80%, which was higher than that in the APS power and APS ECO modes. On the other hand, PDE, TE, and fuel consumption when using APS ECO were around 77.57%, 58.44%, and 19.39 L/h, respectively, which were higher than those of the conventional mode, but lower than those of the APS power mode. Furthermore, the comparative analysis showed that the working loads in the APS ECO mode were located in the ungoverned region and were very close to the engine’s maximum torque, which could allow sudden and unwanted engine turn-off due to the fluctuations in working loads, which is to be avoided. The fuel consumption was also comparatively low. However, the working loads in the conventional and APS power modes were located in the governed region, which was outside the engine’s operating range. Therefore, we recommend that users operate tractors in the APS ECO engine mode for rotary tillage, considering fuel economics and high working loads.